Narratives of HIV: measuring understanding of HIV and the law in HIV-positive patients. Issue 1 (14th January 2015) - Phillips, Matthew D; Schembri, Gabriel
Abstract : Objective: This study aimed to identify the understanding of people living with HIV and AIDS (PLWHA) regarding the application of the law around transmission of HIV in England and Wales. Design: A questionnaire was designed to prompt participants attending a large HIV department to discuss their understanding of the law with reference to HIV transmission. The design focused on qualitative analysis as there were insufficient data available to inform a metric reflecting quantitative data on PLWHA's understanding of the legal implications of transmission. Methods: The data were collected from PLWHA attending their HIV outpatient appointment to ensure relevance of population to the analysis. The answers were analysed using grounded theory and thematic analysis to identify key themes and theories for further testing. Results: Analysis demonstrated that understanding of legal obligations and outcomes of prosecutions was poor and patchy, with behavioural restrictions often overstated. There was a strong theme of ownership of responsibility amongst PLWHA, and of reference to principles of morality beyond legal restrictions. Conclusions: PLWHA remain at risk of prosecution through poor understanding of the law. Clinical services and advocacy agencies should strive to increase understanding in order to enable PLWHA to comprehend the law and negotiate it successfully. This information should be shared as a process, not an isolated event.